CFD analysis of an enhanced nozzle designed for plasma figuring of large optical surfaces - Yu, Nan; Jourdain, Renaud; Gourma, Mustapha; Shore, Paul (European Society for Precision Engineering and Nanotechnology, 2016)
For addressing the correction of Mid Spatial Frequency (MSF) errors on metre scale optical surfaces induced by sub aperture figuring process, a new generation of non-contact plasma based surface figuring tools has been created at Cranfield University. In this context, this paper presents an investigation that focuses on novel enhanced nozzles that were created for a Radio Frequency (RF) Inductively Coupled Plasma (ICP) torch. The characteristics of plasma jet delivered by prototype nozzle and a selected enhanced nozzle are compared using an in-house created CFD model. The enhanced nozzle design is based on the results previously obtained throughout a numerical analysis that enabled to identify the key design aspects of these nozzles. This enhanced nozzle is predicted to provide 12.5% smaller footprint and 15.5% higher temperature.
Keywords: Plasma jet; surface figuring; MSF; De-Laval nozzle; energy beam; optical fabrication; material removal footprint